Nitrogen compounds balance and microbial protein synthesis in supplemented crossbred dairy cows in pasture - Gutierrez, Gabriela Santistevan; Lana, Rogério de Paula; Teixeira, Cesar Roberto Viana; Rennó, Luciana Navajas; Veloso, Cristina Mattos (Acta Scientiarum. Animal Sciences, 2018)
The objective this work was to evaluate the supplementation of cows on Brachiaria decumbens pasture during the rainy-dry transition. Eight 1/2 Holstein/Zebu cows (497 ± 50 kg) were distributed in two 4 x 4 Latin squares, with 2 x 2 factorial treatments (100% mineral salt versus nitrogen salt containing 25:25:50% urea: corn: mineral salt, and 1.5 versus 3.0 kg d-1 concentrate per cow). The experiment lasted 56 days, divided into four periods of 14 days, the last seven days for data collection. No interaction effect (p > 0.05) was detected between the supplement and the different levels of concentrate for any of the evaluated variables. No effect (p > 0.05) of supplement or concentrate level was observed on urinary excretions of purine derivatives, microbial nitrogen compounds and microbial efficiency. Nitrogen salt increased (p < 0.05) nitrogen intake and increased urinary nitrogen excretion, leading to a reduced nitrogen balance, while the higher concentrate level increased (p < 0.05) nitrogen intake and the total amount of nitrogen excreted in milk. Therefore, it is recommended, for crossbred cows in the rainy-dry transition period, the supply of 1.5 kg d-1 concentrate during milking, using only mineral salt instead of nitrogen salt at will on pasture.